New faces in a changing America : multiracial identity in the 21st century - Winters, Loretta I.; DeBose, Herman L. (Sage Publications, 2002)
"New Faces in a Changing America is a comprehensive, penetrating, authoritative, and provocative examination of what it means to be multiracial in this country. With contributions by the leading thinkers, activists, and researchers on the subject, it admirably links theory and the powerful lived experiences of mixed-race people. This book will be the most important reference source on the subject for many years."--James P. Allen, California State University, Northridge New Faces in a Changing America examines the multiracial experience, its history and the political issues and conseq.